Avian Salmonellosis and Colibacillosis: Risk Factors, Antibiotic Resistance, Public Health Impact and Biological Control - Aguidissou , O.N.C.; Akpo, Y.; Adoko, A.M.J.; Adoligbé, C.M.; Koutinhouin, B.G.; Boko, C.K.; Farougou, S. (International Journal of Poultry Science, 2022)
Salmonella spp. and Escherichia coli are the two leading causes of foodborne bacterial zoonosis in the world. Respectively responsible for avian pullorosis/typhosis and colibacillosis in poultry, these pathogens represent major constraints for the poultry industry (layers, broilers) in the world because of the mortality and economic losses generated. The isolation of multidrug resistant Salmonella and E. coli strains in poultry farms in several parts of the world reflects the global aspect of the problem. Antibiotics are essential in the treatment and control of these two bacterial diseases. Resistance results in the progressive ineffectiveness of several families of antibiotics, which constitutes a threat to animal health, food safety and public health. This article reviews the various studies conducted on avian salmonellosis and colibacillosis. The antibiotic molecules to which Salmonella spp. and Escherichia coli strains are resistant are discussed. The virulence and resistance genes associated with the different serotypes are reported. Finally, the risk factors, the impact on public health and some pyhtotherapeutic solutions are described. A better knowledge of this information will allow the poultry industry to make further progress in the elimination of salmonellosis and avian colibacillosis, the reduction of antibiotic use and the potential public health risks.